Excision of oral mucoceles using a chalazion clamp: a case series - Filho, Elias Antonio da Silva; Lemos , Celso Augusto; Mendes, Filipe Santos Ferreira; Silva, Vinicius Teixeira (Journal of Oral Diagnosis, 2025)
Mucocele is the most common minor salivary gland benign disorder in the oral cavity. Different techniques to treat mucoceles have been presented and the conventional surgical approaches, such as excision and marsupialization, may present challenges related to bleeding and surgery duration. This paper reports highlighting its advantages in soft tissue stabilization and hemostasis. Three patients with oral mucoceles in the lower lip underwent excision using the chalazion clamp. This tool facilitated the tissue stabilization, effective hemostasis and reduced the surgical time. None of the patients reported postoperative paresthesia, and no lesion recurrences were observed during the follow-up periods, which ranged from one to five years. The chalazion clamp, commonly used in ophthalmology, provides compression and stabilization, minimizing intraoperative bleeding and improving the surgical precision because it clearly defines the area of the surgery. Its use in mucocele excision allowed selective removal of the minor salivary glands while eliminating the need for an additional assistant. The clamp also enhanced surgical visibility and control, leading to improved outcomes. The application of clamp in mucocele surgery presents a promising, cost-effective alternative which enhances procedural efficiency and patient safety.